Standardization as a catalyst for open and responsible innovation - Arta Pīlēna; Iveta Mežinska; Inga Lapiņa (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Standardization, based on scientific and technological development, provides solutions for optimal level of order in a wide range of industrial, societal and environmental fields. Analogically to the process of open innovation, the development of standards brings together the knowledge and experience of different stakeholders, resulting in solutions that are relevant and accessible to the general public. Similarly, the concept of responsible innovation requires a variety of stakeholders to be involved in innovation development to ensure that their present and future needs are met. Although the link between standardization and innovation is a widely explored issue, the interaction of standardization with the increasingly relevant concepts-open innovation and responsible innovation-remains a research gap, therefore the aim of the study is to identify the common characteristics of standardization and open and responsible innovation, as well as to analyze the interaction between these concepts. The research is based on a literature review on the concepts of standardization, standards development and open, responsible innovation, as well as a field analysis on the ongoing activities in standardization in relation to innovation. The similarities and interaction between standards development and the creation of open, responsible innovation is analyzed and as a result a model that combines the characteristics of standardization, open and responsible innovation and their interrelation is provided. The findings of the study demonstrate that both the standardization process itself and its outcomes can be compared to the processes of open and responsible innovation and can also be characterized as a contributor for creating the environment for the achievement of sustainable development and fostering open and responsible innovation.
Keywords: 650; standardization; standards development; open innovation; responsible innovation; stakeholder involvement; standardization research